The Effects of Atorvastatin on Arterial Stiffness in Male Patients with Type 2 Diabetes. (30th April 2015) - Davenport, Colin; Ashley, David T.; O'Sullivan, Eoin P.; McHenry, Claire M.; Agha, Amar; Thompson, Christopher J.; O'Gorman, Donal J.; Smith, Diarmuid
Abstract : Statin therapy improves lipid profiles and reduces vascular inflammation, but its effects on central arterial stiffness in type 2 diabetes are unclear. The aim of this study was to determine whether statin therapy reduces central arterial stiffness, in a dose-dependent manner, in male patients with type 2 diabetes. Fifty-one patients ceased statin therapy for 6 weeks, followed by randomisation to either 10 or 80 mg of atorvastatin. At randomization, 3 and 12 months, central arterial stiffness was measured via carotid-femoral pulse wave velocity (PWV), along with serum markers of vascular inflammation including high-sensitivity c-reactive protein (hsCRP) and osteoprotegerin (OPG). PWV decreased from 10.37 ± 1.30 to 9.68 ± 1.19 m/sec (p < 0.01 from baseline) at 3 months and 9.10 ± 1.17 m/sec (p < 0.001 from baseline) at 12 months. hsCRP and OPG decreased significantly at 3 and 12 months. Reductions in PWV did not differ significantly between the groups. Baseline PWV and OPG values correlated strongly (r = 0.48, p < 0.01 ), as did their response to atorvastatin over 12 months (r = 0.36 delta-OPG and delta-PWV, p < 0.01 ). Atorvastatin therapy appeared to reduce central arterial stiffness in male type 2 diabetes, with no dose-dependent effect observed. The correlation observed between reductions in PWV and OPG suggests that atorvastatin reduces PWV via direct anti-inflammatory effects on the vasculature.